AB0512 Use of Nominal Group Technique To Facilitate Item Reduction for Sle Classification Criteria Development. (15th July 2016) - Johnson, S.; Khanna, D.; Cervera, R.; Costedoat-Chalumeau, N.; Gladman, D.D.; Hahn, B.H.; Hiepe, F.; Sanchez-Guerrero, J.; Massarotti, E.; Boumpas, D.; Costenbader, K.; Daikh, D.; et al.
Abstract : Background: Criteria for the classification of SLE are being developed with the support of EULAR and ACR. Two independent exercises (expert-based Delphi exercise and data-driven cohort evaluation of early SLE and controls) were undertaken to generate candidate criteria, and then reduce them to a smaller set. Objectives: To select a set of items that maximizes the likelihood of SLE in a person with an uncertain diagnosis. Methods: A panel of seven international SLE experts (reflecting practice in Spain, France, Germany, United States, Canada and Mexico) was asked to rank 41 candidate criteria nominated in the Delphi and cohort studies. The rankings were presented at a face-to-face meeting of the expert panel and steering committee. A consensus meeting using nominal group technique (NGT) was conducted to reduce the list of criteria for consideration. Redundant or poorly performing criteria were removed. Results: This expert panel NGT exercise reduced the candidate criteria for SLE classification from 41 to 21. The panel distinguished potential "entry criteria", which would be required for classification, from other potential "additive criteria", summarized in Table 1 . Entry criteria were ANA by hep 2 immunofluorescence ≥1:80, and low C3 and/or low C4. Additional work is needed to refine definitions*, to evaluate their independence and relationships within domains, and to ascertain item weights. Conclusions: This expert panel NGT exercise resulted in 21 candidate SLE classification criteria. Refinement of definitions, ability to cluster criteria into domains and weighting of criteria will be ascertained in the next phase. Acknowledgement: This work was supported by EULAR and ACR Disclosure of Interest: None declared